Analysis of Taiganja Semiotics in the Kailinese - Alfisyahr; Gazali; Ulinsa; Efendi; Agustan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research aims to analyze the symbolic and philosophical meaning contained in taiganja, one of the cultural objects that has important value in the life of the Kaili tribe in Central Sulawesi. The type of research used is descriptive qualitative research. The method used in this study is a qualitative method. The data collection techniques used in this study are: 1) Observation (Observation), 2) Interview, 3) Documentation. The technical data analysis in this study is data reduction, data presentation, and conclusion drawn. The results of this study show that taiganja is not just jewelry or decorative objects, but a symbol of identity, social status, and spirituality of the Kaili community. The shape of the taiganja circle symbolizes the cycle of life and balance between humans and nature, while the ornaments contain the meaning of fertility, strength, and protection. Philosophically, taiganja reflects the life view of the Kaili people who uphold harmony, togetherness, and respect for ancestors. In addition, this study emphasizes that through semiotic analysis, taiganja can be understood as a system of cultural signs that strengthens the identity and noble values of the Kaili community. This research is expected to contribute to the preservation of local cultural heritage and enrich the study of semiotics in the cultural context of the archipelago.